Practices, knowledge and inter‐professional relationships between speech pathologists and radiation therapists managing patients with head and neck cancer - Hutchison, Alana R. (J Med Radiat Sci, 2019)
INTRODUCTION: This study examined knowledge and practices of speech pathologists (SPs) and radiation therapists (RTs) regarding plan optimisation for head and neck cancer (HNC) patients, and the potential impacts on swallowing function. The secondary aim was to explore the level of interaction occurring between these professional groups within cancer centres. METHODS: Two electronic surveys, with matched questions for SPs and RTs, explored: service/institutional demographics; clinician awareness, practices regarding plan optimisation to swallowing structures and; relationships and interactions between SPs and RTs in the management of HNC patients. Participant recruitment occurred through specialist professional networks with additional snowball sampling. Data were analysed with descriptive statistics and thematic analysis. RESULTS: A total of 32 SPs and 41 RTs completed surveys. All SPs and 50% of RTs were aware of dose‐dysphagia relationships, though SPs rarely used dosimetric information to inform patient management. Only 33% of RTs indicated that their centres actively constrain dose to swallowing structures, reporting that staffing skill mixtures and lack of prescription by the treating RO were restrictive factors. Both SPs and RTs acknowledged the importance of collaborating with colleagues (SPs/RTs) and felt they could assist their colleagues in devising patient management plans, though current collaboration/interaction was minimal. CONCLUSIONS: Levels of awareness were found to be higher in SP group. Despite high levels of awareness, limited use of swallowing structure dose constraints and hence dosimetric information specific to swallowing was rarely used to optimise/guide multidisciplinary HNC acute care. Opportunities for enhanced collaboration between SPs and RTs should be considered.